Probiotics for the prevention and treatment of COVID-19: a rapid systematic review and meta-analysis - Sohail, Aruba; Cheema, Huzaifa Ahmad; Mithani, Maidah Sohail; Shahid, Abia; Nawaz, Ahmad; Hermis, Alaa Hamza; Chinnam, Sampath; Nashwan, Abdulqadir J.; Cherrez-Ojeda, Ivan; Awan, Rehmat Ullah; Ahmad, Sharjeel (Frontiers in Nutrition, 2023)
Background: Although numerous modalities are currently in use for the treatment and prophylaxis of COVID-19, probiotics are a cost-effective alternative that could be used in diverse clinical settings. Hence, we conducted a meta-analysis to investigate the role of probiotics in preventing and treating COVID-19 infection.We searched several databases from inception to 30 May 2023 for all randomized controlled trials (RCTs) and comparative observational studies that evaluated probiotics (irrespective of the regimen) for the treatment or prevention of COVID-19. We conducted our meta-analysis using RevMan 5.4 with risk ratio (RR) and mean difference (MD) as the effect measures.Results: A total of 18 studies (11 RCTs and 7 observational studies) were included in our review. Probiotics reduced the risk of mortality (RR 0.40; 95% CI: 0.25-0.65, I 2 =0%). Probiotics also decreased the length of hospital stay, rate of no recovery, and time to recovery. However, probiotics had no effect on the rates of ICU admission. When used prophylactically, probiotics did not decrease the incidence of COVID-19 cases (RR 0.65; 95% CI: 0.37-1.12; I2=66%). The results for all outcomes were consistent across the subgroups of RCTs and observational studies (P for interaction >0.05).The results of this meta-analysis support the use of probiotics as an adjunct treatment for reducing the risk of mortality or improving other clinical outcomes in patients with COVID-19. However, probiotics are not useful as a prophylactic measure against COVID-19.Large-scale RCTs are still warranted for determining the most efficacious and safe probiotic strains.